OPTIMIZATION OF STR MARKETING STRATEGY OF AGRICULTURAL COMPANIES IN THE REGION BASED ON ARTIFICIAL INTELLIGENCE AND PRINCIPLES OF SMART SPECIALIZATION - KOLOMYTSEVA, Olena; SHEVCHENKO, Nataliia; SERHIIENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the features of optimizing the STP marketing strategy of agricultural enterprises based on artificial intelligence technologies and the principles of smart specialization. The role of segmentation, targeting and positioning to improve the effectiveness of interaction with different groups of consumers is defined. The importance of the implementation of AI for increasing the accuracy of market forecasts and improving communication strategies, which ensures the innovative development of agricultural companies, is substantiated. The role of AI and the concept of smart-specialization separately in the processes of segmentation, targeting and positioning have been studied. The tasks solved by artificial intelligence in ensuring the positioning of agricultural companies on the market are defined and structured. In accordance with the presented wide range of STP-marketing tasks, a system of artificial intelligence tools has been researched, systematized and presented, which includes analytical, prognostic and communication solutions that provide a versatile approach to the implementation of the company's strategy. The tools are grouped by type: tools for tracking social networks; consumer segmentation and personalization tools; predictive analytics platforms; natural language processing (NLP) tools; image and video recognition tools; recommendation systems; tools for competitive analysis; tools for creating and optimizing content; voice search optimization tools; service automation; machine learning algorithms. Their description and application results are given. The advantages of adapting the STP-marketing strategy in accordance with the concept of smart-specialization, which allows agricultural enterprises to use the unique potential of regional resources, contributing to sustainable economic and social development and the integration of environmental standards, are considered.
Keywords: segmentation; targeting; positioning; AI; agricultural enterprises